2017
DOI: 10.2355/isijinternational.isijint-2017-301
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Thermal Diffusivity and Conductivity of FeO Scale Produced on Iron by Thermal Oxidation

Abstract: The thermal diffusivity/conductivity of FeO scales produced on iron substrates by thermal oxidation have been determined as functions of temperature. Iron plates (99.99%) were oxidised at 973 K in air to obtain oxide scales of FeO, Fe 3 O 4 , and Fe 2 O 3 , and then were reduced at 1 273 K in nitrogen to obtain FeO-only. The densities of these scales were 5.85-6.05 g cm − 3 . The laser flash method was used to measure the apparent thermal diffusivity of the whole sample from room temperature to 1 164 K during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 25 publications
1
34
1
Order By: Relevance
“…The value of α FeO,app would be influenced by the thermal boundary resistance between FeO scale and Fe substrate. Li et al 5) have suggested that the boundary resistance is not negligibly small for the FeO scale/Fe at room temperature and they have reported that the boundary resistance for the FeO scale/Fe was 8.3 × 10 − 6 m 2 KW − 1 at room temperature.…”
Section: Effect Of Thermal Boundary Resistance On Thermal Diffusivitymentioning
confidence: 99%
See 4 more Smart Citations
“…The value of α FeO,app would be influenced by the thermal boundary resistance between FeO scale and Fe substrate. Li et al 5) have suggested that the boundary resistance is not negligibly small for the FeO scale/Fe at room temperature and they have reported that the boundary resistance for the FeO scale/Fe was 8.3 × 10 − 6 m 2 KW − 1 at room temperature.…”
Section: Effect Of Thermal Boundary Resistance On Thermal Diffusivitymentioning
confidence: 99%
“…There have been several reports for thermal diffusivities of iron oxides. [2][3][4][5][6] However, the values reported by different laboratories show large discrepancies among them. The discrepancies would be due to the difference in microstructures of samples originating from their preparation methods, i.e., sintering of iron oxide powders 2,3) or thermal oxidation of iron or steel sheets.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations